2016
DOI: 10.12659/ajcr.896790
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effusive Pericarditis due to Horse Chestnut Consumption

Abstract: Patient: Male, 32Final Diagnosis: Pericardial effusion related to the consumption of herbal productSymptoms: DyspneaMedication: Horse chestnut (Aesculus hippocastanum L)Clinical Procedure: Pericardial and pleural effusions were drained through a pericardiopleural windowSpecialty: CardiologyObjective:Unusual clinical courseBackground:There are many well-known causes of pericardial effusion, such as cancer metastasis, bacterial or viral pericarditis, and uremic pericarditis; however, no reports exist in the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The severe symptoms in our case may be due to the consumption of an entire unpurified horse chestnut seed; thus, exposing the body to a substantially high amount of antigen(s). 1,6 The exact mechanism is unclear, but we speculate that the vagus nerve and autonomic nervous system might be implicated in the atrial fibrillation. 7 Previous studies have reported no abnormalities in the levels of liver enzymes and serum/pancreatic amylase.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The severe symptoms in our case may be due to the consumption of an entire unpurified horse chestnut seed; thus, exposing the body to a substantially high amount of antigen(s). 1,6 The exact mechanism is unclear, but we speculate that the vagus nerve and autonomic nervous system might be implicated in the atrial fibrillation. 7 Previous studies have reported no abnormalities in the levels of liver enzymes and serum/pancreatic amylase.…”
Section: Discussionmentioning
confidence: 94%
“…5 In another case, a 32-year-old man had complaints of dyspnea after consuming three boxes of horse chestnut paste over 1.5 months and was diagnosed with acute exudative pericarditis. 6 The possible mechanisms underlying the development of pericardial effusion include the strong antiaggregant effects and the production of antibodies as an immunologic response to horse chestnut antigens. 6 However, in contrast to our case, symptoms in the previous cases did not occur immediately after ingestion, and there were no reports of atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies reported adverse side effects in patients taking HCSE including gastrointestinal tract symptoms, dizziness, nausea, headache, and pruritus, though the reported frequencies were low (0.9–3.0%), and the frequency was not significantly different from that of placebos in three studies [ 122 ]. There was also one case report of pericardial effusion leading to tamponade as a result of the use of horse chestnut paste [ 124 ]. Three hundred milligrams of HCSE (equivalent to 50 mg of escin) taken twice daily for 12 weeks yielded therapeutic effects comparable to compression therapy with regard to edema reduction and can be recommended for patients who cannot otherwise benefit from compressive therapy [ 122 ].…”
Section: Advances In Nonsurgical Management: Conservativementioning
confidence: 99%
“…Ingestion of seeds can cause anaphylaxis (Jaspersen‐Schib, Theus, Guirguis‐Oeschger, Gossweiler, & Meier‐Abt, ; Vega et al., ) and there is a record of a 4‐year‐old boy who died after eating raw horse‐chestnuts (Lampe & Fagerstrom, ). Edem, Kahyaoğlu, and Çakar () also describe a person who developed pericarditis after consuming “3 boxes of horse‐chestnut paste” (no details given) over the previous 1.5 months. Saponins are poorly absorbed in the gut and are largely destroyed by heating, so roasting horse‐chestnuts instead of sweet chestnuts ( Castanea sativa ) is unlikely to cause great harm.…”
Section: Historymentioning
confidence: 99%